The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1525-1403.2010.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Awake vs. Asleep Placement of Spinal Cord Stimulators: A Cohort Analysis of Complications Associated With Placement

Abstract: Abstract:Introduction: Patients will typically undergo awake surgery for permanent implantation of SCS in an attempt to optimize electrode placement using patient feedback about the distribution of stimulation-induced paresthesia. The present study compared efficacy of first-time electrode placement under awake conditions with that of neurophysiologicallyguided placement under general anesthesia. Methods: A retrospective review was performed of 387 SCS surgeries among 259 patients which included 167 new stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
67
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 7 publications
2
67
0
1
Order By: Relevance
“…However, as we observed in our cases of cervical and cervicomedullary SCS that showed a reduction in the amplitude of muscle MEP, we think that inserting an additional volume, i.e. a paddle lead, in the cervicothoracic epidural space has an inherent risk of neurologic injury, and the significance of anatomical consideration and preoperative evaluation of possible cervical stenosis has been emphasized by experienced authors of SCS [16,21,23,26]. …”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…However, as we observed in our cases of cervical and cervicomedullary SCS that showed a reduction in the amplitude of muscle MEP, we think that inserting an additional volume, i.e. a paddle lead, in the cervicothoracic epidural space has an inherent risk of neurologic injury, and the significance of anatomical consideration and preoperative evaluation of possible cervical stenosis has been emphasized by experienced authors of SCS [16,21,23,26]. …”
Section: Discussionmentioning
confidence: 81%
“…Monitoring of CMAP generated by the paddle lead for SCS was reported by Aló [18], Whitworth and Feler [29], Falowski et al [23], and Shils and Arle [21]. The latter authors systematically demonstrated that cervicothoracic SCS electrodes could be placed safely and accurately in 155 patients under general anesthesia using their proposed EMG recording technique, and the electrodes were repositioned intraoperatively in 15.9% of the patients.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations